Efficiency of entomopathogenic bacteria and fungi on Oligonychus yothersi in vitro and on Persea americana Mill. plants - Parco, Jhimy; Valverde-Rodriguez, Agustina; Cornejo, Antonio; Briceño, Henry; Barrionuevo , Laura; Romero , Javier (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
In the germplasm bank of 22 varieties of avocado (Persea Americana Mill.) belonging to the Fruit Horticultural Institute Investigation, HermilioValdizan National University (UNHEVAL)-Peru, it is common to observe a high population of the species Oligonychusyothersi, a phytophagous mite harmful to the crop. Controls with commercial acaricides are restricted in place, due to the presence of beehives installed in adjacent plots. The objective of this study was to evaluate the effect of four commercial formulations containing strains of Metarhiziumanisopliae and Beauveria bassiana and the toxins of Bacillussubtilis, Bacillus thuringiensis var.kurstaki (Btk) for the control of O. yothersi. The entomopathogenic products were evaluated in the field applying a randomized complete block design with five treatments and three replicates. In the laboratory, 500 adult mites were selected, placing 100 mites per Petri dish with three repetitions per treatment. It was found that the formulation Bacillus thuringiensis var.kurstaki under field conditions reduced the population incidence of mites by up to 98.07% in 49 days. In the laboratory, the B. subtilis and M. anisopliae formulations caused 100% mortality six days after application proving to be efficient control alternatives.